Granular Cell Tumor: A Mimicker of Breast Carcinoma - Bosmans, Frederik (J Belg Soc Radiol, 2021)
Teaching point: Granular cell tumors are rare soft tissue tumors that may occur in the breast. While almost always benign, they may mimic a malignant tumor both clinically and on imaging.